New records of Castilleja (Orobanchaceae) in Veracruz, Mexico - Francisco-Gutiérrez, Antonio; Rivera-Hernández, Jaime Ernesto; Vargas-Rueda, Abel Felipe (Instituto de Ecología, A.C., 2016)
Background and Aims: Castilleja nervata and C. tenuiflora var. xylorrhiza were reported for 11 and five states of Mexico, respectively. The aim of this study was to determine the morphological characters of C. nervata in order to differentiate it from C. arvensis, to identify C. tenuiflora var. xylorrhiza as part of the C. tenuiflora complex and separate the latter from C. integrifolia var. integrifolia, as well as showing the geographic distribution and documenting the morphological similitude of these taxa.Methods: Herbaria specimens were revised and the taxa were collected, in addition to measuring and characterizing the morphological structures of the specimens found in the National Park “Cañón del Río Blanco”, which were determined based on literature.Key results: Two taxa of the genus Castilleja unreported previously for the flora of the state of Veracruz, Mexico were identified. Two comparative tables for the identification of the taxa corresponding to the C. tenuiflora complex and for distinguishing between C. arvensis y C. nervata are presented. Photographs and a map of distribution of the new records are also provided.Conclusions: These taxa belong to the 10 species and eight varieties of the genus Castilleja present in Veracruz. Additionally, we recommend to revise the genus in other Mexican states and to continue the botanical exploration of the National Park “Canón del Río Blanco”.